An Active‐Site Sulfonate Group Creates a Fast Water Oxidation Electrocatalyst That Exhibits High Activity in Acid. Issue 3 (17th November 2020) - Nash, Aaron G.; Breyer, Colton J.; Vincenzini, Brett D.; Elliott, Gregory I.; Niklas, Jens; Poluektov, Oleg G.; Rheingold, Arnold L.; Smith, Diane K.; Musaev, Djamaladdin G.; Grotjahn, Douglas B.
Abstract: The storage of solar energy in chemical bonds will depend on pH‐universal catalysts that are not only impervious to acid, but actually thrive in it. Whereas other homogeneous water oxidation catalysts are less active in acid, we report a catalyst that maintained high electrocatalytic turnover frequency at pH values as low as 1.1 and 0.43 ( k cat =1501±608 s −1 and 831±254 s −1, respectively). Moreover, current densities, related to catalytic reaction rates, ranged from 15 to 50 mA cm −2 mM −1 comparable to those reported for state‐of‐the‐art heterogeneous catalysts and 30 to 100 times greater than those measured for two prominent literature homogeneous catalysts at pH 1.1 and 0.43. The catalyst also exhibited excellent durability when a chemical oxidant was used (Ce IV, 7400 turnovers, TOF 0.88 s −1 ). Preliminary computational studies suggest that the unusual active‐site sulfonate group acts a proton relay even in strong acid, as intended. Abstract : Molecular water oxidation catalysts generally suffer in acid and they produce a (much) lower catalytic current than at pH 7, which is a sign of reduced catalytic rate. A sulfonate group introduced to the active site of a molecular complex creates a catalyst that is at least 30 times faster in acid than the analog without a sulfonate group. The electrocatalytic current density produced reaches 50 mA cm −2 per mM.